How do Sustainability-Linked Lending, Fintech-ESG Partnership, and Dynamic Carbon Pricing impact the value of renewable energy projects in Central Java? - Purwanti, Ari; Andiani, Paramita; Bunyamin, Ilham Akbar (Westscience Press, 2025)
This study investigates how sustainability-based financing, fintech–ESG partnerships, and dynamic carbon pricing influence the value of renewable energy projects in Central Java, Indonesia. Using a quantitative approach with 130 respondents from financial institutions, project developers, and government agencies, data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results reveal that all three constructs significantly and positively affect renewable project value, with dynamic carbon pricing showing the strongest direct effect. Furthermore, dynamic carbon pricing mediates the relationships between sustainability-based financing and project value, as well as between fintech–ESG partnerships and project value, indicating that adaptive carbon mechanisms enhance the economic and environmental performance of renewable investments. The findings highlight the synergistic role of financial innovation, digital transparency, and carbon market policies in strengthening the sustainability and competitiveness of renewable energy projects. This study contributes theoretically by integrating Stakeholder Theory, Dynamic Capabilities, and Environmental Economics into a unified framework for sustainable project valuation, and offers practical insights for policymakers and investors in optimizing green finance and carbon pricing strategies across Indonesia’s energy transition agenda.